(untitled) (Albayan Scientific Journal, 2023)
The potato crop is exposed to many diseases and pests that lead to a loss in the amount of the crop, whether in the field or the store, but the physiological defects are considered among the most important factors causing loss in the quality and quantity of the crop. This study was conducted during the period 2020-2021, where this study aimed mainly at evaluating the farmers’ awareness of the physiological defects of potato tubers in the Sirte region through four main aspects: (1) the farmers’ knowledge of the correct concept of physiological defects, (2) the farmers’ knowledge of the most prevalent physiological defects within the field (3) Farmers’ knowledge of the causes of physiological defects, (4) farmers’ knowledge of how to avoid physiological defects affecting potato tubers. This research was based on the personal interview of farmers in collecting data in the five most cultivated areas of the potato crop, namely: Al-Qardabiya area, Al-Haniwa area, Al-Khamseen area, Al-Amra area, Ahrawa area, and that the most cultivated varieties are Asponta and Lajria. The results showed that the most prevalent physiological defects inside the farms are greenness, cracking, small tubercles, secondary growths, lenticels, and finally a hollow heart.. Through this study, it became clear that farmers do not have sufficient knowledge of the term physiological defects, as well as there is a severe decrease in the knowledge of the causes as well as ways to avoid physiological defects, and that such a matter requires exerting more effort to improve the level of farmers’ knowledge of the causes and methods of avoiding the most prevalent physiological defects in potato tubers. Through the implementation of extension programs to familiarize farmers with the concept of physiological defects, as well as the reasons and how to avoid these defects, in order to reduce the loss of the crop and thus raise the productivity and quantity of the crop.